Big Data Analytics for Prostate Radiotherapy - Coates, James; Souhami, Luis; El Naqa, Issam (Frontiers in Oncology, 2016)
Radiation therapy is a first-line treatment option for localized prostate cancer and radiation-induced normal tissue damage are often the main limiting factor for modern radiotherapy regimens. Conversely, under-dosing of target volumes in an attempt to spare adjacent healthy tissues limits the likelihood of achieving local, long-term control. Thus, the ability to generate personalized data-driven risk profiles for radiotherapy outcomes would provide valuable prognostic information to help guide both clinicians and patients alike. Big data applied to radiation oncology promises to deliver better understanding of outcomes by harvesting and integrating heterogeneous data-types, including patient-specific clinical parameters, treatment related dose-volume metrics and biological risk factors. When taken together, such variables make up the basis for a multi-dimensional space (the “RadoncSpace”) in which the presented modelling techniques search in order to identify significant predictors. Herein, we review outcome modelling and big data-mining techniques for both tumor control and radiotherapy-induced normal tissue effects. We apply many of the presented modelling approaches onto a cohort of hypofractionated prostate cancer patients taking into account different data-types and a large heterogeneous mix of physical and biological parameters. Cross-validation techniques are also reviewed for the refinement of the proposed framework architecture and checking individual model performance. We conclude by considering advanced modelling techniques that borrow concepts from big data analytics, such as machine learning and artificial intelligence, before discussing the potential future impact of systems radiobiology approaches.